A Lived Experience of Being A Family Caregiver for People with Schizophrenia in Indonesia; A Phenomenological Study - Gunawan, Indra; Huang, Xuan-Yi; Restiana, Nia; Rosnawanty, Rossy (Indonesian Journal of Global Health Research, 2024)
The family caregiver is significant in helping their relatives with schizophrenia by providing care support. At the same time, the long period and constant caregiving process can negatively affect the caregiver's condition physically and mentally. Understanding these phenomena is needed to create an appropriate intervention to solve the caregiving issues. Objective: This study aimed to explore family caregivers' experiences in providing care for family members with schizophrenia in Indonesia. Method: This study uses a phenomenological qualitative approach conducted from July to December 2022 in West Java, Indonesia. Fourteen primary caregivers were recruited using purposive sampling, meaning they have lived with the client for at least one year, are close relatives, and bear almost all of the care duties. An in-person face-to-face interview was driven to gather the data by following semi-structured questions as a reference. The narrative was analyzed by adopting the seven steps of Colaizzi's method. Results: Three themes and nine sub-themes were identified: lack of support in caregiving, lose yourself, and caregiving burden. Conclusions: These study findings provided a deep understanding of the experiences of Indonesian family caregivers in providing care to family members with schizophrenia at home.